Preventing necroptosis by scavenging ROS production alleviates heat stress-induced intestinal injury. (1st January 2020) - Li, Li; Tan, Hongping; Zou, Zhimin; Gong, Jian; Zhou, Junjie; Peng, Na; Su, Lei; Maegele, Marc; Cai, Daozhang; Gu, Zhengtao
Abstract: Background: Worldwide heat stroke incidence has increased in recent years and is associated with high morbidity and mortality. Therefore, it is critical to identify mechanisms that mediate heat stroke. Previous studies suggested that damage to the small intestine may be a major factor in heat stroke-related morbidity and mortality. However, the mechanism underlying heat stroke related small intestine injury remains unclear. Methods: To explore how heat stroke promotes intestinal damage, we applied two well established models: mouse and IEC-6 cells heat stress (HS) to mimic heat stroke both in vivo and in vitro . The percentages of viability and cell death were assessed by WST-1 and LDH release assays. Induction of HS-induced cell death was analyzed by flow cytometry with Annexin V-FITC/PI staining. Flow cytometry was used to analyze HS-induced mitochondrial superoxide with MitoSOX staining. Malondialdehyde (MDA) levels and superoxide dismutase (SOD) levels were detected by ELISA. Flow cytometry was used to analyze HS-induced mitochondrial depolarization (low ΔΨm ) with JC-1 staining. Histopathology changes in the ileum were detected by H&E staining.The ileum ultrastructure was observed by transmission electron microscopy (TEM). RIPK1, RIPK3, phosphorylated MLKL, and MLKL levels were detected by Western blot. RIPK1-RIPK3 complexes were measured by immunoprecipitation assay. Results: HS increased both necrotic cell rate and RIPK1, RIPK3, and phosphorylated MLKL expression levels in IEC-6 cells. These increased expression levels promoted higher RIPK1-RIPK3 complex formation, leading to necrosome formation both in vivo and in vitro . Moreover, HS caused dyshomeostasis, an oxidative stress response, and mitochondrial damage, along with small intestinal tissue injury and cell death. However, IEC-6 cells or mice pretreated with the RIPK1 activity chemical inhibitor Nec-1 or RIPK3 activity chemical inhibitor GSK'872 significantly reversed these phenomena and promoted balance in oxidative stress response homeostasis. More importantly, the reactive oxygen species (ROS) scavenger N-acetyl-L-cysteine (NAC) pretreatment significantly inhibited HS-induced RIPK1/RIPK3-dependent necroptosis formation both in vivo and in vitro, suggesting that preventing necroptosis via scavenging ROS production might alleviate HS-induced small intestinal tissue injury and cell death. Conclusion: This study provides strong evidence that HS causes damage to both the small intestine and intestinal epithelial cells, scavenging ROS production can significantly alleviate such RIPK1/RIPK3-dependent necroptosis, mediating HS-induced intestinal damage both in vitro and in vivo . These findings provide a clear target for future mechanism-based therapeutic strategies for patients diagnosed with heat stroke.